Familial support in integrated treatment with antiretroviral therapy and medications for opioid use disorder in Vietnam: A qualitative study. Issue 1 (1st December 2022) - Brown, Patrick C. M.; Dinh, Thị Thanh Thuy; Edsall, Andrew; Nguyen, Thu Hang; Mai, Pham Phuong; Hoffman, Kim; Bart, Gavin; Korthuis, P. Todd; Le, Minh Giang
Abstract: Background : Patients report that familial support can facilitate initiation and maintenance of antiretroviral therapy (ART) and medications for opioid use disorder (MOUD). However, providing such support can create pressure and additional burdens for families of people with opioid use disorder (OUD) and HIV. We examined perspectives of people with HIV receiving treatment for OUD in Vietnam and their family members. Methods : Between 2015 and 2018, we conducted face-to-face qualitative interviews with 44 patients and 30 of their family members in Hanoi, Vietnam. Participants were people living with HIV and OUD enrolled in the BRAVO study comparing HIV clinic-based buprenorphine with referral to methadone treatment at 4 HIV clinics and their immediate family members (spouses or parents). Interviews were professionally transcribed, coded in Vietnamese, and analyzed using a semantic, inductive approach to qualitative thematic analysis. Results : Family members of people with OUD and HIV in Vietnam reported financially and emotionally supporting MOUD initiation and maintenance as well as actively participating in treatment. Family members described the burdens of supporting patients during opioid use, including financial costs and secondary stigma. Conclusions : Describing the role of family support in the lives of people living with OUD and HIV in the context of Vietnam enriches our understanding of their experiences and will support future treatment efforts targeting the family unit.